Synthesis and Spectroscopic Properties of New Benzimidazole Schiff Bases - Dincer , Sebla; Ozbay, Seda (Asian Journal of Chemistry, 2012)
Four new ortho-hydroxy Schiff bases of aminobenzimidazoles were synthesised and keto-enol tautomerism were studied using spectroscopic techniques such as UV-VIS, 1H NMR, IR and GC-MS. The results suggest that the salicylaldimine Schiff bases exist predominantly in enol form and the naphthaldimines can coexist in the keto enol tautomeric forms.